The Possible Role of Bruton Tyrosine Kinase Inhibitors in the Treatment of COVID-19: A Review - Mitra Rezaei, MD; Saghar Barati, Pharm-D, PhD; Abdolreza Babamahmoodi, MD; Farzaneh Dastan, Pharm-D, PhD; Majid Marjani, MD (Elsevier, 2022)
ABSTRACT: Background: Coronavirus disease 2019 (COVID-19), an acute, sometimes severe respiratory illness caused by a novel coronavirus has led to a vast pandemic with an astonishing spread rate. Its treatment is unknown, its mortality is significant, and its socioeconomic complications are uncontrollable. Although there is still little known about the pathogenesis of the disease, severe cases of COVID-19 are usually associated with cytokine release syndrome and high serum levels of inflammatory cytokines, which are believed to be a major cause of mortality in these patients. Different pathways cause inflammation and the release of cytokines. One of these pathways is the Bruton tyrosine kinase (BTK) pathway, which is essential for the production of several anti-inflammatory cytokines. Theoretically, the inhibition of BTK signaling can reduce cytokine levels and subsequent anti-inflammatory effects. Objective: This review aims to investigate the role of the BTK pathway in the pathogenesis of COVID-19 and the possible effects of its inhibition in the treatment of this disease. Methods: This narrative review provides information regarding the use of BTK inhibitors in patients with COVID-19 and discusses whether clinicians should consider these medications while managing their patients based on the literature. Data were gathered using the PubMed, Scopus, and Web of Science databases. Results: Some data support the use of BTK inhibitors for treating COVID-19. Conclusions: It is recommended that patients continue their medications in this class if they develop COVID-19 and were receiving these agents before the disease developed. The use of BTK inhibitors might enable patients to experience less severe immune responses to the COVID-19. Well-designed studies are needed to evaluate the effectiveness of BTKis in the management of COVID-19. (Curr Ther Res Clin Exp. 2022; 82:XXX-XXX) © 2022 Elsevier HS Journals